Abortion and the NHS: the first decade. Issue 6158 (27th January 1979) - Fowkes, F G; Catford, J C; Logan, R F
Abstract : Analysis of statistics published since the Abortion Act showed that from 1972 about half the abortions carried out on residents of England and Wales had been performed within the National Health Service. Regional variations in the proportions of abortions performed within the NHS had persisted. In some health regions fewer abortions were being carried out than before. In 1975 about 40% of abortions on single women and women with no existing children were performed within the NHS. Trends in the concurrent sterilisation rate, gestational age at operation, duration of stay in hospital, and mortality and complication rates suggested a steady improvement in the effectiveness and efficiency of abortion services. Nevertheless, the NHS still compares poorly with the private sector and some other countries.